Extracellular enzyme stoichiometry reveals the carbon and phosphorus limitations of microbial metabolisms in the rhizosphere and bulk soils in alpine ecosystems - Cui, Yongxing; Bing, Haijian; Fang, Linchuan; Jiang, Mao; Shen, Guoting; Yu, Jialuo; Wang, Xia; Zhu, He; Wu, Yanhong; Zhang, Xingchang (Plant and soil, 2021)
Aims Alpine ecosystems are important terrestrial carbon (C) pools, and microbial decomposers play a key role in cycling soil C. Microbial metabolic limitations in these ecosystems, however, have rarely been studied. The objectives of this study are to reveal the characteristics of microbial nutrient limitation, and decipher the drivers in the alpine ecosystems. Methods Models of extracellular enzymatic stoichiometry were applied to examine and compare the metabolic limitations of the microbial communities in bulk and rhizosphere soils along an altitudinal gradient (2800–3500 m a.s.l.) under the same type of vegetation ( Abies fabri ) on Gongga Mountain, eastern Tibetan Plateau. Results The soil microbial communities suffered from relative C and phosphorus (P) limitations in the alpine ecosystem despite of high soil nutrient contents here. Partial least squares path modelling (PLS-PM) revealed that the limitations were directly regulated by soil nutrient stoichiometry, followed by nutrient availability. The C and P limitations were higher at the high altitudes (3000–3500 m) than that at the low altitude (2800 m), which mainly attribute to changes of soil temperature and moisture along the altitudinal gradient. This suggested that global warming may relieve microbial metabolic limitation in the alpine ecosystems, and then is conducive to the retention of organic C in soil. Furthermore, the C and P limitations varied significantly between the bulk and rhizosphere soils at the high altitudes (3200–3500 m), but not at the low altitudes. This indicated the influences of vegetation on the microbial metabolisms, while the influences could decrease under the scenario of global warming. Conclusions Our study suggests that the alpine ecosystems with high organic C storage harbour abundant microbial populations limited by relative C and P, which have sensitive metabolic characteristics. This could thus potentially lead to large fluctuations in the soil C turnover under climate change. The study provides important insights linking microbial metabolisms to the environmental gradients, and improves our understanding of C cycling in alpine ecosystems.